Home visits of the nurse and its relationship with hospitalization by diseases sensitive to primary health care - Mayra Romélia Leite Garcia; Daniel Souza Sacramento; Hadelândia Milon de Oliveira; Maria Jacirema Ferreira Gonçalves (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: To identify if nurses' home visits recorded by the family health strategy are proportional to the registered population and the population covered by the family health team, and its relationship with the rate of hospitalization for conditions sensitive to primary health care. Method: Secondary data were gathered from the Information Systems of Primary Care and Hospitalization regarding potential population coverage, number of visits done, hospitalizations for diseases sensitive to primary health care. An exploratory analysis was performed with data grouping for triennium (2010-2012 and 2013-2015) and assignment of scores for each variable, creating the classification strata in: low, medium and high. Results: It was identified that the number of registered home visits does not meet the estimated population coverage as well as does not impact on the admissions sensitive to primary health care. Conclusion and implications for practice: Even with high coverage of the family health strategy, home visits are not the main focus of nurses yet. Home visits should be used as a tool for disease prevention and health promotion, which may explain the non-reduction of hospitalizations sensitive to primary health care.